(untitled) (Proceedings of the International Conference on Education, 2021)
Many adaptations had to be made to classes worldwide amid the COVID-19 pandemic and keeping students engaged and interested in class became a priority for educators. This pandemic has posed a challenge since it forced schools to rapidly migrate the teaching-learning process to an online platform. Particularly, Gen-Z class engagement has been an issue for most teachers, because students tend to rapidly drift away from class; this, alongside the anxiety and stress over the future and the health of their loved ones, has made class engagement an even greater challenge. Using social media as a tool in class may seem unorthodox but given the main features that distinguish Gen-Z, it can be a useful tool to approach and engage them. In order to do so, three different phases of educational innovations were implemented, coronabunker, teaching with memes, and open thread. Each implementation built on the learnings from the previous one, to develop strategies targeted for the participants. The results indicated that students perceive these implementations as fun, when developing the posts from the thread activity, students stated that it also allowed them to integrate curricular content. This generation shares unique language and cultural references that may provide educators a rare glimpse to approach and start to build a bridge that would eventually diminish the gap between generations.